Mapping the social network architecture of rural communities - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Research to understand and design ways that can harness the full potential of social networks. The study is designed in such a way to include participatory and inter-disciplinary research. These include: Qualitative methods of data collection. Focus groups meeting with men and women farmers in the two study locations (Aurepalle and Kanzara) were conducted to understand the important transactions that people have in these two villages. The qualitative surveys were also aimed to understand the villagers’  perceptions  about  Technological,  policy-related changes and development programs in the village over the past two or three decades.